2014
DOI: 10.1007/s00421-014-2891-0
|View full text |Cite
|
Sign up to set email alerts
|

Ramp-incremented and RPE-clamped test protocols elicit similar VO2max values in trained cyclists

Abstract: The RPE-clamped test protocol was as effective as the ramp-incremented protocol for eliciting VO2max and could be considered as a valid alternative protocol, particularly where a fixed test duration is desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 40 publications
8
34
0
Order By: Relevance
“…The reliability of the SPV protocol is further demonstrated using ICC (all >0.80), SEM and RC analyses for V˙O2max and other variables of interest (Table 2). Accordingly, this study confirms that the application of a single SPV, which to date, has been the only way the test has been implemented previously [16], may be appropriate for gauging V˙O2max. However, as the ICC and RC's were shown to improve with trial familiarisation (Table 2), and as participants ran, on average, faster and further during SPV3 than either SPV1 (4.3 & 3.1%, respectively) or SPV 2 (2.8 & 1.6%, respectively), there may be benefit in repeat assessments.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The reliability of the SPV protocol is further demonstrated using ICC (all >0.80), SEM and RC analyses for V˙O2max and other variables of interest (Table 2). Accordingly, this study confirms that the application of a single SPV, which to date, has been the only way the test has been implemented previously [16], may be appropriate for gauging V˙O2max. However, as the ICC and RC's were shown to improve with trial familiarisation (Table 2), and as participants ran, on average, faster and further during SPV3 than either SPV1 (4.3 & 3.1%, respectively) or SPV 2 (2.8 & 1.6%, respectively), there may be benefit in repeat assessments.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, SPV1, SPV2 and SPV3 elicited similar V˙O2max values to those obtained from a traditional laboratory-based GXT. Accordingly, and in support of the study hypotheses, a field-based SPV test may be considered a valid test of V˙O2max, in keeping with previous laboratory-based research [46]. Furthermore, the SPV test was considered reliable, as a period of trial familiarisation did not statistically moderate the V˙O2max or pacing response elicited.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This study also received criticisms over flawed methods and lack of control, attributing findings to using different modes (motorized versus nonmotorized treadmill) and neglect of measurement error to test their hypothesis [83, 8789]. Follow-up studies have shown a higher VO 2 max attainment during self-pacing using a cycle ramp protocol [90], similar VO 2 max attainment using motorized treadmill [83, 91–93] and cycle protocols [84, 94], and a lower VO 2 max attainment using an automated treadmill [89]. It is important to note that findings showing no difference between self-paced and traditional protocols demonstrate the potential utility for self-paced GXT protocols, particularly when considering protocol duration.…”
Section: Vo2max Protocol Paradigm Shiftmentioning
confidence: 99%
“…The SPV has been shown to allow young participants to achieve a higher when compared to a standard incremental exercise test in both cycling and running exercise modes (Astorino et al 2015; Mauger and Sculthorpe 2012; Mauger et al 2013), although a mechanistic explanation is yet to be identified. However, not all studies have found differences in when comparing the SPV vs. standard incremental exercise protocols (Chidnok et al 2013; Faulkner et al 2015; Straub et al 2014). …”
Section: Introductionmentioning
confidence: 99%